Preparation and characterization of mesoporous cerium oxide for toxic As(V) removal: performance and mechanistic studies - Sahu, Uttam Kumar; Mandal, Sandip; Sahu, Sumanta; Gouda, Narayan; Patel, Raj Kishore (Journal of Environmental Engineering and Landscape Management, 2022)
In the present work, the adsorption of carcinogenic pentavalent arsenic (As(V)) from an aqueous solution was studied using mesoporous cerium oxide (MCO). The MCO was synthesized in the precipitation process and confirmed by FT-IR, SEM-EDX, XRD, and BET instrumental techniques. Batch adsorption showed that 95% of As(V) was removed in the optimum conditions of 0.60 g/L adsorbent dose, 10 mg/L initial concentration, time 30 min, and pH 3. Pseudo-secondorder kinetics and the Langmuir isotherm model were fitted to the experimental data. The MCO had a high surface area of 191.97 m2/g and a maximum adsorption capacity of 58.25 mg/g at pH 3. MCO could be able to remove 88% and 82% in the first and second cycles after being desorbed with 0.1 M NaOH solution. The Zeta potential and FTIR studies suggested that electrostatic attraction and ligand exchange mechanisms were responsible for As(V) adsorption.